2017
DOI: 10.1038/srep40280
|View full text |Cite
|
Sign up to set email alerts
|

IK acts as an immunoregulator of inflammatory arthritis by suppressing TH17 cell differentiation and macrophage activation

Abstract: Pathogenic T helper cells (TH) and macrophages have been implicated in the development of rheumatoid arthritis (RA), which can lead to severe synovial inflammation and bone destruction. A range of therapies have been widely used for RA, including specific monoclonal antibodies and chemical inhibitors against inflammatory cytokines produced by these cells. However, these have not been sufficient to meet the medical need. Here, we show that in transgenic mice expressing truncated IK (tIK) cytokine, inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Although our previous study showed that tIK is a candidate target for inflammatory arthritis treatment [4], we did not then have a method for delivery of exogenous tIK into patients. In this study, we developed the recombinant AAV2-tIK for this purpose and showed that it has potential as a therapeutic agent for suppressing the progression of inflammatory arthritis.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Although our previous study showed that tIK is a candidate target for inflammatory arthritis treatment [4], we did not then have a method for delivery of exogenous tIK into patients. In this study, we developed the recombinant AAV2-tIK for this purpose and showed that it has potential as a therapeutic agent for suppressing the progression of inflammatory arthritis.…”
Section: Modelmentioning
confidence: 99%
“…immunologically activated condition, but not in a normal condition [4]. Therefore, AAV2-tIK may not show any immunological response in a normal condition in the mouse.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous study demonstrated the effects of tIK on rheumatoid arthritis (RA) using three mouse models: interleukin (IL)-1 receptor antagonist knockout (IL1RaKO) mice, an autologous induced RA model, and IL1RaKO/tIK-transgenic mice, termed tIK-IL1RaKO mice [ 11 ]. We observed milder symptoms and lower severity of RA in tIK-IL1RaKO mice compared with IL1RaKO mice.…”
Section: Introductionmentioning
confidence: 99%